Born into an isolating world: family-centred care for babies born to mothers with COVID-19. (February 2023) - Dowse, G.; Perkins, E.J.; Stein, H.M.; Chidini, G.; Danhaive, O.; Elsayed, Y.N.; Carvalho, W.B.; AlNaqeeb, N.; Rooze, S.; Cetinkaya, M.; Vetter-Laracy, S.; Pilar-Orive, F.J.; et al.
Summary: Background: The benefits of facilitating breastmilk feeding and close contact between mother and neonate (family-centred care; FCC) in the perinatal period are well-established. The aim of this study was to determine how the delivery of FCC practices were impacted for neonates born to mothers with perinatal SARS-CoV-2 infection during the COVID-19 pandemic. Methods: Neonates born to mothers with confirmed SARS-CoV-2 infection during pregnancy were identified from the 'EsPnIC Covid paEdiatric NeonaTal REgistry' (EPICENTRE) multinational cohort between 10 March 2020 and 20 October 2021. The EPICENTRE cohort collected prospective data on FCC practices. Rooming-in and breastmilk feeding practice were the main outcomes, and factors influencing each were determined. Other outcomes included mother-baby physical contact prior to separation and the pattern of FCC components relative to time and local site guidelines. Findings: 692 mother-baby dyads (13 sites, 10 countries) were analysed. 27 (5%) neonates were positive for SARS-CoV-2 (14 (52%) asymptomatic). Most sites had policies that encouraged FCC during perinatal SARS-CoV-2 infection for most of the reporting period. 311 (46%) neonates roomed-in with their mother during the admission. Rooming-in increased over time from 23% in March–June 2020 to 74% in January–March 2021 (boreal season). 330 (93%) of the 369 separated neonates had no FCC physical contact with their mother prior, and 319 (86%) were asymptomatic. Maternal breastmilk was used for feeding in 354 (53%) neonates, increasing from 23% to 70% between March–June 2020 and January–March 2021. FCC was most impacted when mothers had symptomatic COVID-19 at birth. Interpretation: This is the largest report of global FCC practice during the COVID-19 pandemic to date. The COVID-19 pandemic may have impacted FCC despite low perinatal transmission rates. Fortunately, clinicians appear to have adapted to allow more FCC delivery as the COVID-19 pandemic progressed. Funding: The National Health and Medical Research Council (Australia): Grant ID 2008212 (DGT), Royal Children's Hospital Foundation : Grant ID 2019–1155 (EJP), Victorian Government Operational Infrastructure Support Program.